Cultures of thinking in action 10 mindsets to transform our teaching and students' learning - Ritchhart, Ron (Jossey-Bass, 2023)
According to a 2020 survey by Georgetown University, 96% of employers say that critical thinking and active listening are extremely important to success. Critical thinking is a skill used not only in occupations, but everyday life. Given this, it is no surprise that past studies have found a strong correlation between critically thinking about subjects and high academic success. Ron Ritchhart argues that being able to think critically about the world is more important than any particular subject or fact a student might learn. While it is important to learn specific details, critical thinkers are equipped to face any scenario with greater success than those who are not taught the skill. Creating a Culture of Thinking is all about making sure schools foster critical thinking skills"-- Provided by publisher.